a, 2x^2 - 6x
=> 2x^2 - 6x = 0
=> 2x ( x - 3 ) = 0
=> 2x = 0 hoặc x - 3 = 0
=> x = 0 : 2 hoặc x = 0 + 3
=> x = 0 hoặc x = 3
Vậy đa thức trên có 2 nghiệm là x = 0 hoặc x = 3
b, 3x^2 + 9x
=> 3x^2 + 9x = 0
=> 3x ( x + 9 ) = 0
=> 3x ( x + 3 ) = 0
=> 3x = 0 hoặc x + 3 = 0
=> x = 0 : 3 hoặc x = 0 - 3
=> x = 0 hoặc x = -3
Vậy đa thức trên có 2 nghiệm là x = 0 hoặc x = -3
c, x^2 + 4x + 3
=> x^2 + 4x + 3 = 0
=> x^2 + 3x + x + 3 = 0
=> ( x^2 + 3x ) + ( x + 3 ) = 0
=> x ( x + 3 ) + ( x + 3 ) = 0
=> ( x + 1 ) ( x + 3 ) = 0
=> x + 1 = 0 hoặc x + 3 = 0
=> x = 0 - 1 hoặc x = 0 - 3
=> x = -1 hoặc x = -3
Vậy đa thức trên có 2 nghiệm là x = -1 hoặc x = -3